Gold Investments – Regression Analysis of the Gold Price Over a Certain Period - Yaneva, Mariya (Research Papers, 2023)
The global development of the monetary and financial system has evolved over different historical periods. Increasingly, the subject of discussions among economic subjects are the ways to increase their financial well-being through investments in the financial markets. One of the most preferred ways to preserve and increase the financial wealth of individuals is investments in precious metals, in this case – gold, which are realized in specialized financial markets for raw materials. In this regard, the subject of discussions and analyzes in the present development is gold (researched in a global investment aspect), as an element of financial markets and a way of investing, and the subject is emphasized on regression analyzes related to its price values and author’s forecasts for future periods from time.